Interstitial lung diseases and autoimmunity - E. L. Nasonov; L. P. Ananyeva; A. S. Belevsky (Научно-практическая ревматология, 2025)
Lung disease is one of the most common manifestations of systemic autoimmune rheumatic diseases (SARDs), involving all parts of the respiratory system in the pathological process. Interstitial lung diseases (ILD) are of great importance and often lead to the development of progressive pulmonary fibrosis (PPF). The following clinical categories of patients are distinguished within ILDs associated with SARDs (ILD-SARDs): ILD in patients with a reliable diagnosis of SARDs; ILD as the first manifestation of SARDs; ILD or interstitial pneumonia with autoimmune features. Clinical phenotypes of ILD-SARDs vary from «asymptomatic» to «rapidly progressing» are related with risk factors for progressive lung damage. These phenotypes should be considered for conducting clinical, laboratory and instrumental screening and prescribing anti-inflammatory or antifibrotic therapy. In the pulmonology practice a patient with ILD may have previously established SARDs, or this diagnosis could be suspected based on a number of clinical symptoms of rheumatic diseases. Problem of ILD-SARDs diagnostic is very complex, which determines a multidisciplinary approach based on the interaction with rheumatologists, pulmonologists and radiologists. The possibilities and perspectives for pharmacotherapy of ILD-SARDs are based on the rational use of anti-inflammatory, immunomodulatory and antifibrotic drugs. The following issues related to pharmacotherapy of ILD-SARDs should be emphasized: identification of patients with a rapidly progressing phenotype of pulmonary fibrosis; the contribution of inflammatory activity; the effectiveness of therapy in relation to the leading “extrapulmonary” manifestations of SARDs and pneumotoxicity within the implementation of the “treat to target” concept. The greatest achievement in the pharmacotherapy of autoimmune diseases is associated with the use of chimeric antigen receptor (CAR) T-cell therapy, which mechanism is associated with the elimination of pathogenic autoreactive B-cells. Preliminary data of CAR T-cell therapy indicate the high efficacy in a wide range of clinical manifestations of SARDs, including the progression of ILD in patients with systemic sclerosis and antisynthetase syndrome, and there are strong evidence of the important role of autoimmune mechanisms in the pathogenesis of ILD.